The Implementation of Piaget’s and Vygotsky’s Theories in Supporting the Cognitive Development of Children in Raudhatul Athfal (RA) and Kindergarten - farihatul Atikah; Nur Saidah; Eva Latipah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2026)
This article discusses the importance of cognitive development in early childhood as a crucial phase that establishes the foundation for subsequent learning and intellectual growth. The study emphasizes the application of Jean Piaget and Lev Vygotsky’s theories to support cognitive development through constructive, collaborative, and experiential approaches. Additionally, the role of family and educational environments in stimulating children’s thinking, imagination, and social skills is explored in depth. The utilization of science-based play, verbal stimulation, and optimal social interaction is believed to enhance children’s critical thinking and problem-solving abilities. This research aims to serve as a reference for parents, educators, and researchers in developing effective strategies to optimize early childhood cognitive development.